Diagnostic Features for Human Categorisation of Adult and Child Faces - Faghel-Soubeyrand, Simon; Kloess, Juliane A.; Gosselin, Frédéric; Charest, Ian; Woodhams, Jessica (Frontiers in Psychology, 2021)
Knowing how humans differentiate children from adults has useful implications in many areas of both forensic and cognitive psychology. Yet, how we extract age from faces has been surprisingly underexplored in both disciplines. Here, we used a novel data-driven experimental technique to objectively measure the facial features human observers use to categorise child and adult faces. Relying on more than 35,000 trials, we used a reverse correlation technique that enabled us to reveal how specific features which are known to be important in face-perception––position, spatial-frequency, and orientation––are associated with accurate child and adult discrimination. This showed that human observers relied on evidence in the nasal bone and eyebrow area for accurate adult categorisation, while they relied on the eye and jawline area to accurately categorise child faces. For orientation structure, only facial information of vertical orientation was linked to face-adult categorisation, while features of horizontal and, to a lesser extent oblique orientations, were more diagnostic of a child face. Finally, we found that spatial-frequency diagnosticity showed a U-shaped pattern for face-age categorisation, with information in low and high spatial frequencies being diagnostic of child faces, and mid spatial frequencies being diagnostic of adult faces. Through this first characterisation of the facial features of face-age categorisation, we show that important information found in psychophysical studies of face-perception in general (i.e. the eye area, horizontals, and mid-level spatial-frequencies) is crucial to the practical context of face-age categorisation, and present data-driven procedures through which face-age classification training could be implemented for real-world challenges.